A ceramic particle reinforced high entropy alloy composite coating and preparation method thereof
By using ceramic particles to enhance the CoCrFeNiMn high-entropy alloy composite coating in the aerospace field, the problem of insufficient wear resistance of existing high-entropy alloys at room temperature is solved, and the high hardness and wear resistance are improved, and it has important application potential.
Patent Information
- Application Number
- CN202410617089.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-17
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-05-17
AI Technical Summary
The wear resistance of existing CoCrFeNiMn high entropy alloys at room temperature is not sufficient to meet the requirements in the aerospace field.
The method of enhancing high-entropy alloy composite coating of ceramic particles is used to mix CoCrFeNiMn high-entropy alloy powder with WC ceramic powder, and the coating is prepared on the surface of the TC4 matrix using laser melting deposition technology. The WC ceramic particles act as reinforced phases to improve the hardness and wear resistance of the coating.
It achieves high hardness and excellent wear resistance, and is suitable for aerospace, marine engineering and other fields.
Smart Images

Figure CN118563196B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of wear-resistant coatings, and in particular relates to a ceramic particle reinforced high-entropy alloy composite coating and a preparation method thereof. Background Art
[0002] With the rapid development of the aerospace field, the structural and functional requirements of materials are no longer limited to a single high-performance indicator, but require them to have high comprehensive performance in complex working environments. TC4, as a typical lightweight alloy for aviation, has the advantages of low density and high specific strength, but its low hardness and poor wear resistance limit its further application in the aerospace field.
[0003] Applying functional coatings on the surface of parts can significantly improve the hardness and wear resistance of parts, thereby extending the stability and service life of parts. CoCrFeNiMn high entropy alloy is a mixture of five elements, Co, Cr, Fe, Ni and Mn, in nearly equiatomic ratios. The resulting alloy does not form a complex intermetallic compound, but a simple solid solution structure. Multiple elements are evenly distributed in the lattice, with a high configuration entropy at the atomic level, which increases the thermodynamic stability of the alloy and makes the high entropy alloy show a unique microstructure and excellent physical, chemical and mechanical properties. CoCrFeNiMn is considered to be the most classic and widely used high entropy alloy system so far, but its wear resistance at room temperature still cannot fully meet the requirements in the aerospace field. Summary of the invention
[0004] Technical issues to be solved:
[0005] In order to avoid the shortcomings of the prior art, the present invention provides a ceramic particle reinforced high entropy alloy composite coating and a preparation method thereof. The coating is prepared by mixing CoCrFeNiMn high entropy alloy powder containing five elements of Co, Cr, Fe, Ni and Mn and WC ceramic powder. The WC ceramic particles are used as the reinforcement phase of the high entropy alloy, and the high entropy alloy is used as the matrix and bonding phase of the WC ceramic. A coating having the comprehensive properties of the CoCrFeNiMn high entropy alloy and the WC ceramic is developed, which has high hardness and excellent wear resistance, and has important application potential in the fields of aerospace, marine engineering, etc.
[0006] The technical solution of the present invention is: a ceramic particle reinforced high entropy alloy composite coating, characterized in that: it comprises CoCrFeNiMn high entropy alloy powder and WC ceramic powder, wherein the mass proportion of the WC ceramic powder is 1% to 20%;
[0007] The CoCrFeNiMn high entropy alloy powder has five elements of Co, Cr, Fe, Ni and Mn in an equal molar ratio.
[0008] A further technical solution of the present invention is: the particle size of the CoCrFeNiMn high entropy alloy powder is 45 to 105 μm.
[0009] A further technical solution of the present invention is that the particle size of the WC ceramic powder is 45 to 105 μm.
[0010] A further technical solution of the present invention is that the mass proportion of W element in the WC ceramic powder is 75% to 85%.
[0011] A method for preparing a ceramic particle reinforced high entropy alloy composite coating, characterized in that the specific steps are as follows:
[0012] CoCrFeNiMn high entropy alloy powders were prepared by vacuum gas atomization.
[0013] The WC ceramic powder was prepared by plasma spheroidization method;
[0014] The CoCrFeNiMn high entropy alloy powder and the WC ceramic powder are fully mixed by a low-energy vacuum ball milling method to obtain a composite powder raw material; the mass proportion of the WC ceramic powder in the composite powder is 1% to 20%;
[0015] WC particle reinforced CoCrFeNiMn high entropy alloy composite coating was prepared on the surface of TC4 substrate by laser melting deposition technology.
[0016] A further technical solution of the present invention is: when the low-energy vacuum ball milling method is used to prepare the composite powder raw material, it must be carried out under vacuum conditions, the ball milling jar has a capacity of 500 ml, 100 g of composite powder and 400 g of zirconia grinding balls are used, the rotation speed is 200 rpm, and the operating time is 4 hours.
[0017] A further technical solution of the present invention is that before the coating is prepared on the surface of the TC4 substrate, the TC4 substrate needs to be sandblasted.
[0018] A further technical solution of the present invention is: the process parameters of the laser melting deposition technology are: laser power of 1300W, spot diameter of 3.5mm, laser scanning speed of 10mm / s, powder feeding speed of 6.5g / min, adjacent laser scanning spacing of 1.92mm, and the corresponding overlap rate of 40%.
[0019] A further technical solution of the present invention is: the method for preparing CoCrFeNiMn high entropy alloy powder by vacuum gas atomization is as follows:
[0020] Put five kinds of metal raw materials, Co, Cr, Fe, Ni and Mn, into the crucible of vacuum gas atomization equipment, start the vacuum system, and the vacuum degree reaches the set value;
[0021] Heating the crucible heats the metal raw material to above the melting point to ensure that the metal is completely melted;
[0022] Argon gas is injected into the crucible through a gas nozzle to form a layer of gas mist on the metal surface. The high-speed gas flow ejects the liquid metal into tiny droplets.
[0023] After atomization, the droplets cool rapidly and solidify into spherical powder particles, which fall freely onto the collector;
[0024] The prepared powder is sieved to remove particles that are too large or too small, and powder particles with a particle size of 45 to 105 μm are collected.
[0025] A further technical solution of the present invention is that the mass proportion of WC ceramic powder in the composite powder is 1% to 10%.
[0026] Beneficial Effects
[0027] The beneficial effect of the present invention is that the present invention provides a method for preparing a tungsten carbide hard particle reinforced high entropy alloy composite coating, wherein Co, Cr, Fe, Ni and Mn are transition elements, and the alloy formed by their combination presents a single-phase FCC structure, forming a stable solid solution, and there are no "solute atoms" and "solvent atoms" in the traditional sense. Different metal atoms occupy lattice positions with the same probability, and the performance of the alloy is enhanced by solid solution strengthening. Since the electronegativity, crystal structure and atomic radius of each element are different, this will inevitably produce more serious lattice distortion, so that the high entropy alloy has higher strength and hardness.
[0028] The present invention adopts a "two-step method" to prepare the powder raw material, that is, first prepare the high entropy alloy powder to form a stable FCC structure solid solution, and then mix it with spherical tungsten carbide particles by ball milling, and use the high entropy alloy as the bonding phase of WC to better retain the tungsten carbide particles in the coating. Different from the design and application of the traditional metal reinforcement phase, the present invention uses tungsten carbide particles with a particle size similar to that of the high entropy alloy powder as the reinforcement phase. This first ensures the uniformity of the particle size and morphology of the mixed powder, avoids the appearance of "satellite powder", makes the powder raw material have a higher sphericity, significantly reduces the probability of clogging of the laser cladding powder feeding system during the preparation of the coating, and improves the efficiency of powder preparation; secondly, the tungsten carbide particles with a larger particle size are more conducive to resisting the stress generated during friction and wear in the coating, which can further improve the wear resistance of the coating.
[0029] The coating prepared by the present invention has excellent comprehensive properties of high hardness and wear resistance, and has important application value in the fields of national defense, aerospace, marine engineering, nuclear industry, etc. The present invention provides an application example of the above coating on the surface of lightweight titanium alloy for aviation. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 3 is a morphology diagram of the CoCrFeNiMn high entropy alloy spherical powder used in the embodiment of the present invention.
[0031] Figure 2 3 is a morphology diagram of the WC ceramic spherical powder used in the embodiment of the present invention.
[0032] Figure 3 These are the WC ceramic reinforced high entropy alloy composite powder image and W element spectrometer scanning image prepared in Example 3; (a) morphology image of WC ceramic reinforced high entropy alloy composite powder, (b) W element scanning image. DETAILED DESCRIPTION
[0033] The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, but should not be construed as limiting the present invention.
[0034] Based on the fact that the wear resistance of the high entropy alloy coating prepared in the prior art at room temperature cannot fully meet the requirements of the aerospace field, the present invention provides a ceramic particle reinforced high entropy alloy composite coating, including CoCrFeNiMn high entropy alloy powder and WC ceramic powder (such as Figure 1 and Figure 2 ), wherein the mass proportion of WC ceramic powder is 1% to 20%; and the five elements of Co, Cr, Fe, Ni and Mn in the CoCrFeNiMn high entropy alloy powder are in an equal molar ratio.
[0035] Specifically, the particle size of the CoCrFeNiMn high entropy alloy powder is 45 to 105 μm, preferably 65 to 85 μm.
[0036] Specifically, the particle size of the WC ceramic powder is 45 to 105 μm, preferably 65 to 85 μm.
[0037] Specifically, the mass proportion of W element in the WC ceramic powder is 75% to 85%.
[0038] Preferably, the mass fraction of WC powder is 1% to 10%.
[0039] The present invention provides a method for preparing a WC ceramic particle reinforced CoCrFeNiMn high entropy alloy composite coating, which specifically comprises the following steps:
[0040] Step 1: preparing CoCrFeNiMn high entropy alloy powder by vacuum gas atomization method;
[0041] The five metal raw materials of Co, Cr, Fe, Ni and Mn in equal molar ratios are preliminarily cleaned to remove impurities;
[0042] Place the raw materials into the crucible of the vacuum gas atomization equipment, start the vacuum system, and ensure that the equipment reaches the required vacuum degree;
[0043] Heating the crucible heats the metal raw material to above the melting point to ensure that the metal is completely melted;
[0044] Argon gas is injected into the crucible through a gas nozzle to form a layer of gas mist on the metal surface. The high-speed gas flow ejects the liquid metal into tiny droplets.
[0045] After atomization, the droplets cool rapidly and solidify into spherical powder particles, which fall freely onto the collector;
[0046] The prepared powder is screened to remove particles that are too large or too small, and powder particles with a particle size of 45 to 105 μm are collected;
[0047] Step 2: preparing WC ceramic powder by plasma spheroidization method;
[0048] The WC ceramic powder prepared by plasma spheroidization has a particle size of 45 to 105 μm, and the mass fraction of W element in the powder is 75% to 85%. The WC ceramic powder used in the present invention has a similar powder particle size to the CoCrFeNiMn high entropy alloy powder, which helps to improve the stability of the powder feeding process in the subsequent laser melting deposition process.
[0049] Step 3: Fully mix the CoCrFeNiMn high entropy alloy powder and the WC ceramic powder by low-energy vacuum ball milling to obtain a composite powder raw material; Figure 3 As shown;
[0050] CoCrFeNiMn high entropy alloy powder and WC ceramic powder of different mass ratios are weighed, and the mass fraction of WC powder is 1% to 10%. The present invention limits the content of WC ceramic powder to the above range, which helps to form a composite coating with higher bonding strength and better comprehensive performance. The increase in the content of WC reinforcing phase helps to improve the overall hardness and wear resistance of the composite coating, but too high a content of WC reinforcing phase will lead to a decrease in the bonding strength of the prepared coating and prone to cracking.
[0051] 100 g of the mixed powder and 400 g of zirconium oxide grinding balls were placed in a stainless steel ball mill with a volume of 500 ml, and the ball mill was evacuated.
[0052] An omnidirectional planetary ball mill was used for powder mixing at a rotation speed of 200 rpm and a continuous operation time of 4 hours to finally produce WC ceramic reinforced CoCrFeNiMn high entropy alloy powder.
[0053] Step 4: Use laser melting deposition technology to prepare WC particle reinforced CoCrFeNiMn high entropy alloy composite coating on the surface of TC4 substrate.
[0054] The composite coating is prepared by laser melting deposition, and the substrate is TC4 titanium alloy for aviation. Before laser melting deposition, the substrate is sandblasted and the substrate surface is cleaned with anhydrous ethanol. In the present invention, the parameters of the laser melting deposition system are preferably: laser power is 1300W, spot diameter is 3.5mm, laser scanning speed is 10mm / s, powder feeding speed is 6.5g / min, adjacent laser scanning spacing is 1.92mm, and the corresponding overlap rate is 40%.
[0055] The present invention provides a WC ceramic particle reinforced CoCrFeNiMn high entropy alloy composite coating prepared by the above technical solution, and its application in aerospace equipment.
[0056] The above technical solution is further described below through specific examples and drawings:
[0057] The particle size of the CoCrFeNiMn high entropy alloy powder used in the following examples and comparative examples is 45 to 105 μm, and the content of each element in the high entropy alloy is an equimolar ratio; the particle size of the selected WC ceramic powder is 45 to 105 μm, and the mass proportion of the W element is 80%.
[0058] Embodiment 1:
[0059] 99g of CoCrFeNiMn high entropy alloy powder and 1g of WC ceramic powder were selected and placed in a 500ml stainless steel ball mill with 400g of zirconia grinding balls, and the ball mill was vacuumed. The powder was mixed at a speed of 200rpm and a continuous operation time of 4 hours to obtain a composite powder. Then the coating was prepared on the TC4 substrate. The laser melting deposition system parameters were: laser power of 1300W, spot diameter of 3.5mm, laser scanning speed of 10mm / s, powder feeding speed of 6.5g / min, adjacent laser scanning spacing of 1.92mm, and the corresponding overlap rate of 40%.
[0060] Embodiment 2:
[0061] 95 g of CoCrFeNiMn high entropy alloy powder and 5 g of WC ceramic powder were selected and placed in a stainless steel ball mill with a volume of 500 ml with 400 g of zirconia grinding balls, and a coating was prepared according to the method in Example 1.
[0062] Embodiment 3:
[0063] 90 g of CoCrFeNiMn high entropy alloy powder and 10 g of WC ceramic powder were selected and placed in a stainless steel ball mill with a volume of 500 ml with 400 g of zirconia grinding balls, and a coating was prepared according to the method in Example 1.
[0064] Comparative Example 1:
[0065] TC4 titanium alloy substrate for aviation use without coating deposited on the surface.
[0066] Comparative Example 2:
[0067] 100 g of CoCrFeNiMn high entropy alloy powder was selected without mixing with WC ceramic powder, and was placed in a stainless steel ball mill with a volume of 500 ml with 400 g of zirconia grinding balls, and a coating was prepared according to the method in Example 1.
[0068] Comparative Example 3:
[0069] 85 g of CoCrFeNiMn high entropy alloy powder and 15 g of WC ceramic powder were selected and placed in a stainless steel ball mill with a volume of 500 ml with 400 g of zirconia grinding balls, and a coating was prepared according to the method in Example 1.
[0070] Comparative Example 4:
[0071] 80 g of CoCrFeNiMn high entropy alloy powder and 20 g of WC ceramic powder were selected and put into a stainless steel ball mill with a volume of 500 ml with 400 g of zirconia grinding balls, and a coating was prepared according to the method in Example 1.
[0072] Test Example 1
[0073] The Vickers hardness tester was used with a load of 50 gF and a holding time of 15 s to measure the hardness at different locations of the prepared coating and take the average value. The wear resistance of the embodiment was tested using a liquid metal friction and wear tester. The grinding ball was selected to have a diameter of 6 mm. 3 N 4 Grinding ball, normal load 30N, friction rate 2Hz, stroke 1mm, friction time 30min.
[0074] Table 1 Performance test results of embodiments and comparative examples
[0075]
[0076] It can be seen from Table 1 that the WC ceramic reinforced CoCrFeNiMn high entropy alloy composite coating prepared in the present invention has high surface hardness and excellent wear resistance, and can play a good protective role on the substrate surface.
[0077] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and intent of the present invention.
Claims
1. A method for preparing a ceramic particle reinforced high entropy alloy composite coating, characterized in that: 90g of CoCrFeNiMn high entropy alloy powder and 10g of WC ceramic powder were selected and placed in a stainless steel ball mill with a volume of 500ml with 400g of zirconia grinding balls, and the ball mill was vacuumed. The powders were mixed at a speed of 200rpm and a continuous operation time of 4 hours to obtain a composite powder; then the coating was prepared on the TC4 substrate, and the parameters of the laser melting deposition system were: laser power of 1300W, spot diameter of 3.5mm, laser scanning speed of 10mm / s, powder feeding speed of 6.5g / min, adjacent laser scanning spacing of 1.92mm, and the corresponding overlap rate of 40%; CoCrFeNiMn high entropy alloy powders were prepared by vacuum gas atomization. The WC ceramic powder was prepared by plasma spheroidization method; WC particle reinforced CoCrFeNiMn high entropy alloy composite coating was prepared on the surface of TC4 substrate by laser melting deposition technology.
2. The method for preparing a ceramic particle reinforced high entropy alloy composite coating according to claim 1, characterized in that: The particle size of the CoCrFeNiMn high entropy alloy powder is 45-105 μm.
3. The method for preparing a ceramic particle reinforced high entropy alloy composite coating according to claim 1, characterized in that: The particle size of the WC ceramic powder is 45 to 105 μm.
4. The method for preparing a ceramic particle reinforced high entropy alloy composite coating according to claim 1, characterized in that: The mass proportion of W element in the WC ceramic powder is 75% to 85%.
5. The method for preparing a ceramic particle reinforced high entropy alloy composite coating according to claim 1, characterized in that: Before preparing the coating on the surface of the TC4 substrate, the TC4 substrate needs to be sandblasted.
6. The method for preparing a ceramic particle reinforced high entropy alloy composite coating according to claim 1, characterized in that: The method for preparing CoCrFeNiMn high entropy alloy powder by vacuum gas atomization is as follows: Put five kinds of metal raw materials, Co, Cr, Fe, Ni and Mn, into the crucible of vacuum gas atomization equipment, start the vacuum system, and the vacuum degree reaches the set value; Heating the crucible heats the metal raw material to above the melting point to ensure that the metal is completely melted; Argon gas is injected into the crucible through a gas nozzle to form a layer of gas mist on the metal surface. The high-speed gas flow ejects the liquid metal into tiny droplets. After atomization, the droplets cool rapidly and solidify into spherical powder particles, which fall freely onto the collector; The prepared powder is sieved to remove particles that are too large or too small, and powder particles with a particle size of 45 to 105 μm are collected.
Citation Information
Patent Citations
Laser melting deposition method of ceramic reinforced high-entropy alloy composite component
CN109290572A